VILLAGE INFORMATION SYSTEM OPERATOR JOURNALISM TRAINING IN MANAGING THE GAMPONG COT SEURANI WEBSITE - Deddy Satria M; Masriadi; Riski Aulia; Muhammad Nazar (RADJA PUBLIKA, 2022)
The existence of village information operators is an integral part of village development and development of rural areas, therefore village information systems are specifically regulated in Law Number 16 of 2004 concerning Villages through Article 86. Management of village information in Gampong Cot Seurani is still limited so that maximum results have not been seen. Aside from being a database, the village information system, in this case the role of the village information operator, can also be developed into a community mass media that is managed online between villagers or between other village stakeholders. It is therefore very important to provide basic journalistic training, especially reporting techniques and news writing, to village information operators in Gampong Cot Seurani, Muara Batu District, North Aceh District.